Breast Cancer and Cancer Stem Cells: A Mini-Review. Issue 4 (July 2014) - Filipova, Alzbeta; Seifrtova, Martina; Mokry, Jaroslav; Dvorak, Josef; Rezacova, Martina; Filip, Stanislav; Diaz-Garcia, Daniel
Breast cancer is the most common type of malignant disease in women worldwide. In developing countries the past few years have sustained an increasing incidence of this type of cancer. Currently, breast cancer is the second leading cause of death due to cancer in women. In 2008 alone it was diagnosed in more than 1 million patients and each year the number of breast cancer-related deaths is estimated to be ~450, 000. The mortality rate in breast cancer patients has been decreasing over the years thanks to the development of early diagnostic methods and more effective treatments. But despite the new advances in cancer diagnosis and treatment, the risk of recurrence and metastasis is ever present. It has been theorized that cancer stem cells are involved in the process of tumor growth and metastases. Due to their self-renewing and differentiation capabilities, they are now considered the underlying factor in tumor recurrence and the main reason for therapy resistance. Therefore, the characterization of cancer stem cells may contribute to the development of more effective treatment strategies that should make it possible to eliminate cancer stem cells in order to prevent tumor relapse and metastasis in diagnosed patients.